Viron üks ja kõik - Pajusalu, Renate (Virittäjä, 2004)
The Estonian üks and kõik (englanti) 1/2004 (108) The Estonian ks and kik The article examines the use of the Estonian words ks one and kik all in conversation. The material for the study consists of everyday conversations from a corpus of spoken Estonian. ks and kik are both basic vocabulary operators: they appear frequently, their meaning is schematic and they participate in grammaticalisation processes. Although ks and kik are often used to express the number of referents, they also have other functions in conversation. The writer looks at the various semantic and pragmatic shades of meaning associated with these words in conversational use. Both words form part of reference chains, in the same way as pronouns. Used alone, kik refers to a group whose members function or experience things together. It is often the first mention of the group, and the referent only becomes clear to the listener through the context. Kik can also be given a generic interpretation, when it is used to express general opinions, and it can serve as a particle or be given the meaning finish. Used alone, ks most often requires that the group to which its referent belongs has been defined already, in which case it refers to one of the groups members. Both kik and ks often also appear as noun phrase modifiers. ks indicates that the noun phrase is indefinite, and it thus serves as another Estonian indefinite determiner alongside mingi some. Kik indicates that the referents of the noun phrase form an entity together. As a modifier, ks can also be given the meaning same or about Renate Pajusalu